Experimental and Simulation Study on Breaking Rock under Coupled Static Loading and Ultrasonic Vibration - Yan Zhao; Congshan Zhang; Zengzeng Zhang; Ke Gao; Dajun Zhao; Zihang Sun; Xiaoshu Lv; Yu Zhou; Guobing Zhai (Shock and Vibration)
In recent years, ultrasonic vibration rock-breaking technology has aroused great interest in tunnel excavation and underground mineral. To apply this technology to practical engineering, it is necessary to compare the difference between cumulative damage and crack propagation of rock under static load and ultrahigh frequency alternating load. Numerical simulation and laboratory experimental methods were used in this paper to study the damage and fracture characteristics of rock under static loading and ultrasonic vibration. The variation laws of rock infrared temperature characteristics, porosity and compressive strength under different ultrasonic static loads were studied. The discrete element model of rock under ultrasonic vibration was established, and the numerical simulation was carried out by PFC2D software. We designed the ultrasonic rotary drilling device to verify the drilling effect. The process and mechanism of rock fragmentation under static load and ultrasonic vibration load were analyzed from the perspective of energy. Numerical simulation and experimental results showed that the combination of static load and ultrasonic vibration accelerates the failure speed of rock sample. The thermal infrared temperature characteristic test showed that the rock-breaking process under ultrasonic load and static load has three stages: stage I, elastic deformation and the temperature rises linearly; stage II, the development of microcrack and the temperature is further increased uniformly, and stage III, macrobreaking and rock chips falling off, and the temperature fluctuates sharply. There is a minimum threshold value for the promotion of static loading to break rock by ultrasonic vibration. Only when the static load is greater than 200 N, the crack propagation will occur in the rock sample. At this time, with the increase of static load, the crack propagation will further intensify, and the rock-breaking effect is more obvious. Under the same weight on bit (WOB), the penetration of rotary ultrasonic drilling can be increased by 13.93% ∼ 38.11% compared with conventional rotary drilling.